Gender Semiotics In The Animation Film Cartoon Brave - Eka Putri Augustine (Pena Cendekia Insani, 2020)
This research was conducted to determine how the meaning ofmasculine women in the animated cartoon film made by PixarAnimation Studio and Walt Disney Pictures was conducted todetermine how the theme of this film is a Princess (Princess), entitledBrave. Where this research will see how the image of masculine womenfrom this Brave film. The subject of this research is the Brave film asseen from its narrative structure. Meanwhile, the research object to beanalyzed is the representation of the meaning of masculine women. Inthis study, the researcher will see how the Brave film will break thestereotypes of a royal princess that is usually displayed by Walt Desney.A royal princess (Princess) is usually seen from several things whichinclude physical appearance (physical appearance), style of dress(fashion), character (character) and interaction with the environment(social interaction). Meanwhile, in the Brave film, the findings showthat women like Princess Merida are constructed as open, brave,strong, independent, and tough. In addition, it also manages tomaintain its unique identity without meeting the expectations anddemands of others.